Hemophagocytic lymphohistiocytosis in imported pediatric visceral leishmaniasis in a nonendemic area - Bode, Sebastian F. N.; Bogdan, Christian; Beutel, Karin; Behnisch, Wolfgang; Greiner, Jeanette; Henning, Stephan; Jorch, Norbert; Jankofsky, Martin; Jakob, Marcus; Schmid, Irene; Veelken, Norbert; Vraetz, Thomas; et al. (Journal of Pediatrics, 2014)
To describe characteristics of visceral leishmaniasis-associated hemophagocytic lymphohistiocytosis (HLH) with focus on diagnostic clues and pitfalls, including the frequency of central nervous system (CNS) involvement, and to determine the efficacy of liposomal amphotericin B (L-AmB).We retrospectively analyzed clinical and laboratory features, diagnostic procedures, and treatment of 13 patients with HLH with imported visceral leishmaniasis, reported to the German HLH reference center (1999-2012).The spectrum of presentations was indistinguishable from patients with hereditary HLH or with acquired HLH because of infections with other pathogens. In 8 patients, disease onset occurred before the age of 2 years, coinciding with the typical age of manifestation of primary HLH. Two patients had mild nonspecific CNS findings. Misleading antiviral IgM (n = 6) and autoantibodies (n = 2) led to inaccurate interpretation of the etiology of HLH, sometimes with inappropriate therapeutic consequences. False negative results for Leishmania were obtained by initial bone marrow microscopy in 6/13, serology in 1/12, bone marrow culture in 2/5, and polymerase chain reaction of peripheral blood in 1/3 patients, and all bone marrow samples tested were Leishmania-positive by polymerase chain reaction (n = 7). L-AmB was administered to 12 patients, 5 of whom had no prior HLH-directed immunosuppressive therapy; sodium stibogluconate was administered to 1 patient. Persistent remission was achieved in 11 cases. Two patients required repeated or prolonged L-AmB therapy.Awareness of diagnostic pitfalls may save patients from unnecessary toxic treatment. CNS involvement is rare. L-AmB shows efficacy in visceral leishmaniasis-associated HLH.
EVALuna2:7654